Multidisciplinary Management of Severe Traumatic Hepatic Injury Involving Interventional Radiology Embolization, Trauma Laparotomy, and Liver Transplantation. Issue 5 (May 2023) - Shah, Jigesh; Mufti, Arjmand; Dumas, Ryan; Porembka, Matthew; Minei, Joseph; Hanish, Steven I.; Vagefi, Parsia A.
This report describes liver transplantation as a successful strategy in the management of a young man who presented to a local emergency room following catastrophic traumatic hepatic vascular injuries. Expeditious multidisciplinary management, including interventional radiology, trauma surgery, and ultimately transplant surgery, provided the patient with definitive therapy following his injuries and early return to normal activity. Our experience highlights the importance of prompt referral of select hepatic trauma patients for liver transplant evaluation as part of their complex trauma management.